Evaluation of Phenolic Compounds and Antioxidant and Antimicrobial Activities of Some Common Herbs - Muhammad Abdul Qadir; Syeda Kiran Shahzadi; Asad Bashir; Adil Munir; Shabnam Shahzad (International Journal of Analytical Chemistry)
The study was designed to evaluate the phenolic, flavonoid contents and antioxidant and antimicrobial activities of onion (Allium cepa), garlic (Allium sativum), mint (Mentha spicata), thyme (Thymus vulgaris), oak (Quercus), aloe vera (Aloe barbadensis Miller), and ginger (Zingiber officinale). All extracts showed a wide range of total phenolic contents, that is, 4.96 to 98.37 mg/100 g gallic acid equivalents, and total flavonoid contents, that is, 0.41 to 17.64 mg/100 g catechin equivalents. Antioxidant activity (AA) was determined by measuring reducing power, inhibition of peroxidation using linoleic acid system, and 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging activity. Different extracts inhibited oxidation of linoleic acid by 16.6–84.2% while DPPH radical scavenging activity (IC50 values) ranged from 17.8% to 79.1 μg/mL. Reducing power at 10 mg/mL extract concentration ranged from 0.11 to 0.84 nm. Furthermore the extracts of these medicinal herbs in 80% methanol, 80% ethanol, 80% acetone, and 100% water were screened for antimicrobial activity by disc diffusion method against selected bacterial strains, Staphylococcus aureus, Escherichia coli, Bacillus subtilis, and Pasteurella multocida, and fungal strains, Aspergillus niger, Aspergillus flavus, Rhizopus solani, and Alternaria alternata. The extracts show better antimicrobial activity against bacterial strains as compared to fungal strains. Results of various assays were analyzed statistically by applying appropriate statistical methods.